The efficacy of Helicobacter pylori eradication in diabetics and its effect on glycemic control: A systematic review and meta‐analysis. Issue 2 (19th January 2021) - Song, Xin; Cai, Changzhou; Jin, Qi; Chen, Xueyang; Yu, Chaohui
Abstract: Background and Aims: Previous studies have revealed the association between Helicobacter pylori ( H. pylori ) and diabetes mellitus, but conflicts still exist. The present study tried to investigate the underlying link between these two diseases by making comprehensive analyses of the impact of diabetes on H. pylori eradication and the influence of H. pylori eradication on diabetes. Methods: We systematically searched relevant studies from PubMed, Cochrane Library, Web of Science, and Embase updated to April 23, 2020. Studies examining the association between H. pylori eradication and diabetes were included. Pooled odds ratio (OR) and weighted mean differences (WMD) were calculated for different results. Results: Among the 2125 retrieved studies, 36 studies were included. Patients with type 2 diabetes mellitus (T2DM) have higher risk of H. pylori eradication failure than the non‐diabetic one (OR = 2.59, 95% CI 1.82–3.70). Body mass index (BMI) was identified as a major factor affecting the efficacy of H. pylori eradication in diabetics, and better glycemic control was also found in eradication succeed patients (WMD: 0.51, 95% CI 0.20–0.81). Moreover, after eradication of H. pylori, improvement of HbA1c was proved (WMD = −0.33, 95% CI −0.65 to −0.02) in T2DM. Conclusion: A higher risk of H. pylori eradication failure in T2DM was confirmed, and it was associated with BMI and glycemic control. Moreover, we also provided evidence that H. pylori eradication could improve glycemic control in patients with T2DM, which indirectly reflect the interaction between H. pylori and the diabetes.